(Post)pamięciowy aktywizm: Medialne praktyki oporu po rosyjskiej agresji na Ukrainę (Politeja, 2023)
(POST)MEMORY ACTIVISM: MEDIA RESISTANCE PRACTICES AFTER RUSSIA’S INVASION OF UKRAINEThe military aggression of Russia against independent Ukraine has starkly exposed the naivety of the expression “never again,” which has been repeated for over eighty years. The bestiality exhibited by Russian soldiers and the cynical propaganda emanating from the Kremlin since the beginning of the invasion have resulted in both literal and symbolic resistance from the free world and a surge of international solidarity with Ukrainians, both online and off. Notably, there has been an increase in subvertising campaigns targeting brands that have failed to withdraw their products from Russia, as it signifies support for Russian war crimes. Vladimir Putin, often juxtaposed with Hitler as “Putler,” has emerged as a prominent figure on numerous posters, and murals and the butt of memes, while the Kremlin’s foreign policy has explicitly been labeled as Rashism. Active media users have creatively altered, reinterpreted, and enriched cultural texts, generating new content and meanings. The current article examines several examples of visual communication expressing resistance to the Russian regime and its war crimes, along with highlighting the involvement of institutions, brands and media that support it.